Pengaruh Technostress Penggunaan Media Sosial terhadap Tingkat Produktivitas di Era Digital - Nurfadillah, Rizka; Aziz, Syamsuddin; Akbar, Muh. (Universitas Muhammdiyah Yogyakarta, 2025)
The development of digital technology and social media has changed the way Generation Y and Z interact, work, and interpret their daily lives. Amidst the rapid flow of information, a phenomenon known as technostress has emerged, which is psychological pressure arising from the intensity and complexity of technology use. This study aims to analyze the effect of technostress arising from social media use on the productivity levels of Generation Y and Z in Indonesia. The method used is quantitative with 400 respondents analyzed using Partial Least Square (PLS) through SmartPLS 4.0. The research instrument was compiled based on technostress and productivity indicators with a 1–4 Likert scale. The results show that digital pressure is not always negative. On the contrary, in certain contexts, technostress can encourage individuals to adapt more quickly, filter information more selectively, and form effective work strategies. These findings reinforce the concept of techno-eustress, which is a form of positive stress that can trigger increased focus, motivation, and work performance. Thus, social media is not merely a source of distraction but can also be a trigger for productivity when managed wisely. This study contributes theoretically to expanding the understanding of social media-based technostress and emphasizes the importance of digital literacy and awareness of digital health. With the ability to manage digital pressure, individuals can transform stress into productive energy that supports performance in the modern era.